Inggris - Ayu Trisiya, Kapita; Ananda , Rusydi (Universitas Islam Ahmad Dahlan (UIAD), 2025)
Ulos is a traditional woven cloth in the Toba Batak tradition, Ulos functions as an important symbol that symbolizes love, protection and unity. Therefore, this study aims to uncover the values ​​of these plane figures using ethnomathematics. This study employed qualitative methods. Interviewing informants and analyzing Toba Batak ulos (traditional Batak cloth) aimed to explore the cultural values ​​of the Toba Batak people. Then the data was obtained through the interview process, observation and documentation.The data validity technique used was source triangulation. Triangulation techniques are used to test the validity of data. Furthermore, the researcher analyzed data using Toba Batak Ulos, based not only on the researcher's interpretation but also on discussions with cultural experts, informants, and mathematics experts. This study proposes the conceptual values ​​of plane figures found in Sadum, Holong, and Panssamot ulos. In Sadum ulos, the plane figures found are equilateral triangles, rhombuses, and circles. In Holong ulos, the plane figures found are trapezoids and rhombuses. In Panssamot ulos, the plane figures found are pentagons, rectangles, and rhombuses, which are associated with the cultural values ​​of Toba Batak ulos.